2010
DOI: 10.1111/j.1439-0507.2009.01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic and proteinase activities in clinical isolates of Candida parapsilosis and Candida tropicalis with reference to the isolation anatomic site

Abstract: The aim of this study was to determine in vitro haemolytic and protease activities of Candida parapsilosis and Candida tropicalis isolates, obtained from anatomically distinct sites. Analysis of haemolytic activity of C. parapsilosis and C. tropicalis isolates obtained from the same anatomic site revealed that C. tropicalis isolates from blood had statistically higher activity (P < 0.05) than C. parapsilosis. On comparison of haemolytic activities of Candida isolates obtained from different anatomic sites, C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
2
11
0
1
Order By: Relevance
“…França et al 28 investigated the hemolytic activity of C. parapsilosis and C. tropicalis isolated from different human anatomical sites. According to their data, enzymatic activity varies widely from species to species and is associated with the site of isolation.…”
Section: Discussionmentioning
confidence: 99%
“…França et al 28 investigated the hemolytic activity of C. parapsilosis and C. tropicalis isolated from different human anatomical sites. According to their data, enzymatic activity varies widely from species to species and is associated with the site of isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning NCAC species, C. parapsilosis distinct switch phenotypes exhibited differential ability to form biofilm on polystyrene surfaces (Laffey and Butler, 2005). For C. tropicalis, França et al (2010) also found a correlation in phenotypic switching and biofilm formation.…”
Section: Switching Morphotypes: Ultrastructure and Morphological Typesmentioning
confidence: 70%
“…According to Monod and Borg-von [25] Saps play a role in fungal adherence and invasion of skin by C. albicans. The occurrence of Saps has been previously demonstrated in C. parapsilosis isolates obtained from distinct clinical samples [10,[26][27][28] and it has being suggested that Saps are associated in superficial, but not with systemic invasion, caused by C. parapsilosis [26]. They observed the induction of Saps from C. parapsilosis cultivated in media containing bovine serum albumin (BSA) as a nitrogen source.…”
Section: Acid Proteinases Productionmentioning
confidence: 88%
“…We previ-ously reported the production of proteinases and haemolytic factor by isolates of C. parapsilosis obtained from distinct clinical sources [10]. More recently, we have demonstrated that C. parapsilosis sensu stricto secretes a hemolytic factor into culture medium [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation